Analysis Of Drainage Channel Capacity On Prof. M. Yamin Street In Pontianak - Imanuel Kemenangenta Perangin Angin; Ikhwan Arief Purnama; Randy Setiawan (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Surface runoff results from precipitation that is not absorbed or infiltrated into the soil due to water-saturated soil conditions. If left uncontrolled, surface runoff can cause puddles or flooding that may disrupt human activities and the environment. In this study, the research site was located on Prof. M. Yamin Street in the city of Pontianak. In the current study, Prof. M. Yamin Street in Pontianak already has a drainage system; however, the performance of this drainage system’s capacity needs to be analyzed. The method used to analyze the performance of the drainage system on Prof. M. Yamin Street involves comparing the existing drainage capacity against the surface runoff discharge resulting from the average daily maximum rainfall using the rational method and hydraulic analysis. In the analysis of the drainage system on Prof. M. Yamin Street, the drainage system’s capacity is no longer sufficient to accommodate the surface runoff flow rate of 1.1691 m³/s, therefore, it is necessary to modify the dimensions of the drainage channels using hydraulic analysis with a width (B) of 1.4 meters, a channel depth (H) of 0.557 meters, and a channel bank height (W) of 0.528 meters on both sides of Prof. M. Yamin Street.